Searching for the entrepreneurial personality: New evidence and avenues for further research - Marco Caliendo; Alexander S. Kritikos (Institute for the Study of Labor (IZA), 2011)
What makes the entrepreneurial personality is the key question we seek to answer in the special issue of the Journal of Economic Psychology on Personality and Entrepreneurship. The contributions are clustered around questions regarding the linkage between personality, socio-economic factors and entrepreneurial development. Results further explain the gender puzzle, while, at the same time, it is clear that stereotypes of what makes the ideal entrepreneur must be revisited. This conclusion is based on new insights into the effects that variables, such as risk tolerance, trust and reciprocity, the value for autonomy and also external role models, have on entrepreneurial decision making. On a more general note, it is clear that more informative longitudinal data sets at the individual level are needed in order to find conclusive answers. In an ideal world researchers would have access to data that includes personality characteristics and psychological traits, motivational factors and cognitive skills. In this respect the research community needs to find new ways to collect these data and make them available for entrepreneurship research.
urn:nbn:de:101:1-201106224706
Keywords: D81; J23; L26; M13; 330; entrepreneurship; personality characteristics; risk aversion; trust; autonomy